Disgorgement dan Disgorgement Fund: Pemulihan Kerugian dan Perlindungan Investor - Monica Fitriyani Purba; Adi Sulistiyono (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
This research is conducted to analyze the comparison of disgorgement in the US and Indonesia and the regulation of POJK No. 65 /POJK.04/2020 in legal protection for investors. This research is categorized as normative legal research with a statute approach and comparative approach and uses library research techniques from primary and secondary legal sources. The results showed that POJK No. 65 /POJK.04/2020 has the potential to recover investor losses. Nevertheless, the risk of loss still exists mainly due to crimes and violations in the capital market. By implementing the regulation, it is expected to increase investor confidence and strengthen the integrity of the capital market. However, to achieve optimal implementation, further education to investors, transparency in the disgorgement determination process, and an effective monitoring and evaluation system are needed.